DEVELOPMENT OF SCIENCE MODULE BASED ON INQUIRY SCIENCE ISSUES TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Zharfan Afina; Riezky Maya Probosari; Annisa Nur Khasanah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2022)
This study aims to 1) know how to develop modules, 2) know the feasibility of the module, and 3) know the effectiveness of the IPA module with an approach of Inquiry Science Issues on Climate Change Materials to improve the critical thinking skills of students in grade VII junior high school. The development model used in this study is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques using observation methods, interviews, as well as documentation. Quantitative analysis techniques for analyzing data have been validated by experts and module assessments by practitioners and students. In contrast, the analysis of qualitative descriptive data to analyze the resulting module data. The results of the study concluded that 1) Modules developed based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with inquiry science issues that use critical thinking indicators. 2) Module eligibility in terms of validation results Material Expert Module got the same result of 90.27% with categories Excellent, media expert validation of 89.06% and 88.43% respectively with excellent category, practitioner ratings of 88.33% and 87.91% respectively with excellent categories, student ratings of 81.05% with very categories good. 3) The effectiveness of the module analyzed using the N-gain test obtained a result of 0.5014; 0.3 g ? ? 0.7, so the module is said to be effective with a moderate category.